Implementasi Motif Tradisional Kina dari Kabupaten Bandung dalam Desain Bangku Rotan - Bahri, Nurul Fitriana; Muchlis; Setiawan, Oky (UNIVERSITAS INDO GLOBAL MANDIRI, 2025)
This study discusses the designer and manufacture of rattan benches with the application of traditional Kina motifs originating from Bandung Regency. The main focus of the study is to produce a real product in the form of a rattan bench prototype that integrates Kina motifs aesthetically and functionally, so that it not only preserves local cultural heritage but also presents added value in contemporary furniture design. This study uses a design/creation method based on design, with stages of visual exploration of Kina motifs, development of rattan bench design concepts, prototype creation, and evaluation of results through expert and stakeholder interviews to assess the feasibility of the design visually, ergonomically, and culturally. The results of the study in the form of a rattan bench prototype show the success of the integration of Kina motifs, with embossed details on the seat cover and pattern stylization on the rattan frame, which are positively appreciated by local craftsmen and the community. The benefits of this design result include the preservation of traditional motifs in the form of real products, increasing the aesthetic value of local furniture, and developing product potential to support the culture-based creative industry.